Immature Platelet Fraction as A Potential Marker To Differentiate Types of Acute Coronary Syndrome - Endah Indriastuti; Yetti Hernaningsih; Yulia Nadar Indrasari; Andrianto Andrianto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Acute Coronary Syndrome (ACS) includes ST-Elevation Myocardial Infarction (STEMI), non-ST Elevation MyocardialInfarction (NSTEMI), and Unstable Angina (UA). Platelet plays an essential role in ACS pathogenesis. Immature PlateletFraction (IPF) and platelet indices can predict platelet activations. Platelet indices consist of platelet count, Mean PlateletVolume (MPV), Platelet Distribution Width (PDW), plateletcrit (Pct). This study aimed to analyze the differences of IPF andplatelet indices among ACS patients. This study was an observational analytical cross-sectional study conducted inDr. Soetomo Hospital during May-September 2019. The subjects consisted of 30-STEMI, 25-NSTEMI, and 24-UA patients.The EDTA-samples were measured for platelet indices and IPF using Sysmex XN-1000. The differences between IPF andplatelet indices among STEMI, NSTEMI, and UA patients were analyzed using Kruskal-Wallis and Mann-Whitney test. The IPFvalues were significantly higher in STEMI patients than NSTEMI and UA patients. The IPF values of NSTEMI patients werehigher than UA patients. The MPV, PDW, and P-LCR were significantly higher in STEMI and NSTEMI compared to UA. TheMPV, PDW, and P-LCR values of NSTEMI patients were significantly higher than UA patients. The significant differencesbetween STEMI and NSTEMI toward UA might be caused by the more severe thrombotic conditions in myocardial infarctionpatients than UA. The IPF values were significantly different among each type of ACS patients gave an opportunity using thisparameter to differentiate the ACS types. The MPV, PDW, and P-LCR were significantly higher in myocardial infarctionpatients than UA patients, which also allowed them to use those parameters to differentiate both conditions.